Comparison between early versus late pulmonary vein isolation in the management of atrial fibrillation. (14th October 2021) - Intan-Goey, V; Scherrenberg, M; Falter, M; Kaihara, T; Dendale, P; Verwerft, J
Abstract: Background: Atrial fibrillation (AF) is the most common type of arrhythmia. The health burden of AF keeps increasing with the rising incidence of AF caused by the aging population and the high prevalence of unhealthy lifestyle. Pulmonary vein isolation (PVI) is the cornerstone of invasive rhythm control treatment in AF. Randomized controlled trials have shown superiority of an PVI strategy compared to conservative treatment. However, the best timing to perform a PVI to achieve the most optimal outcome is still unknown. Purpose: To investigate whether the timing of performing PVI has consequences for the AF management in terms of medical cost, the number of repeated electrical cardioversion and hospitalisations and mortality. Methods: In this monocentric retrospective observational study, all patients who underwent an electrical cardioversion and PVI between January 2012 and January 2020 were included using a hospital administrative data record. Follow-up data were collected up to a maximum of 67 months. Early PVI is defined as patients receiving a PVI after a first electrical cardioversion; late PVI is defined as patients receiving PVI after more than one electrical cardioversion. We compared the two groups for the mean medical cost, the number of repeated electrical cardioversions performed, any unplanned hospitalization associated with AF and mortality. Results: A total of 407 patients were included in this analysis. Respectively, in the early versus the late PVI strategy groups, the mean age was 64.5 vs. 66.3 years (p=0.105) and the mean follow-up was 1630±843 vs. 2039±781 days (p<0.001). The mean medical cost since the first cardioversion was €8533 vs. €8987 (p=0.503), the number of additional electrical cardioversion performed was 0.4 vs 3.0 (p<0.001) and mortality rate was 2, 8% vs. 0% (p=0.116). The Log-rank analysis showed a significant difference (p<0.001) between both groups in the time to first unplanned hospitalisation on cardiology ward after PVI in favor of early PVI strategy. Conclusions: An early PVI tends to be superior to a late PVI strategy in the management of AF with less need for repeated electrical cardioversion and lower hospitalisation rate. Total medical cost and mortality rate were comparable in both approaches. Funding Acknowledgement: Type of funding sources: None.